Political Change in Liberalism: Carl Poper’s perspective as an example - Abdullah, Kanaan Hamagharib; Shareef, Aryan Rasheed (Journal of University of Human Development, 2021)
Liberalism does not have one perspective on political changes. Classical liberalism places great emphasis on individual freedom and opposes state interference in the private affairs of individuals. From this standpoint, Liberalism accepts revolutionary movements against oppressive regimes that violate individuals’ freedom. The idea of freedom is central in neoliberalism, particularly in social welfares, to provide people decent conditions for pursuing a good life or for human flourishing and therefore the neoliberalism perspective opts for a limited interference by the state in the market. The different perspectives of neoliberalism can trace their roots back to classical liberalism’s arguments, which encourage individuals’ freedom and opt for limit state interference, while in terms of political change, they have conservative views and in this regard, Karl Poper is with the gradual changes of society and rejects the revolutionary mechanism because it threatens freedom and leads to tyranny